2022
DOI: 10.1186/s12916-022-02690-w
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use and contraceptive counselling interventions for women of reproductive age with cancer: a systematic review and meta-analysis

Abstract: Background A lack of clarity exists regarding contraceptive uptake and counselling among women with cancer, despite these women having unique family planning needs. This study aimed to systematically review the available literature and produce an overall summary estimate of contraceptive use and counselling among women with cancer across the cancer care continuum. Methods A systematic search of articles reporting on contraceptive counselling and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Research has found effective modes of contraception are rarely used by WoCBP diagnosed with cancer. 9 Reasons for not using contraception include unconfirmed beliefs regarding infertility and compatibility with imaging or difficulty finding a suitable option. 19 This further highlights the need to ensure adequate pregnancy screening prior to CIT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has found effective modes of contraception are rarely used by WoCBP diagnosed with cancer. 9 Reasons for not using contraception include unconfirmed beliefs regarding infertility and compatibility with imaging or difficulty finding a suitable option. 19 This further highlights the need to ensure adequate pregnancy screening prior to CIT.…”
Section: Discussionmentioning
confidence: 99%
“…7 Patients may want to discuss contraception options with their oncologists or haemotologists as hormones are known to promote the growth of some cancers. 9 Counselling improves contraception uptake if physicians tailor discussions to their patients' diagnosis and treatment path. 20 Contraception should be emphasised as a priority for discussion among oncologists and haematologists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations